A novel role for the dioxin receptor in fatty acid metabolism and hepatic steatosis - Lee, Jung Hoon; Wada, Taira; Febbraio, Maria; He, Jinhan; Matsubara, Tsutomu; Lee, Min Jae; Gonzalez, Frank J; Xie, Wen (Gastroenterology (New York, N.Y. 1943), 2010)
The aryl hydrocarbon receptor (AhR) also known as the dioxin receptor or xenobiotic receptor is a member of the basic helix-loop-helix/period AhR nuclear translocator single minded family. The goal of this study was to determine the endobiotic role of AhR in hepatic steatosis. Wild-type, constitutively activated AhR transgenic, AhR null and CD36/fatty acid translocase null mice were used to investigate the role of AhR in steatosis and the involvement of CD36 in the steatotic effect of AhR. The promoters of the mouse and human CD36 genes were cloned and their regulation by AhR was analyzed. Activation of AhR induced spontaneous hepatic steatosis characterized by the accumulation of triglycerides. The steatotic effect of AhR likely is owing to the combined up-regulation of CD36 and fatty acid transport proteins, suppression of fatty acid oxidation, inhibition of hepatic export of triglycerides, increase in peripheral fat mobilization, and increased hepatic oxidative stress. Promoter analysis established CD36 as a novel transcriptional target of AhR. Activation of AhR in liver cells induced CD36 gene expression and enhanced fatty acid uptake. The steatotic effect of an AhR agonist was inhibited in CD36-/- mice. Our study reveals a novel link between AhR-induced steatosis and the expression of CD36. Industrial or military exposures to dioxin and related compounds have been linked to increased prevalence of fatty liver in human beings. Results from this study may help to establish AhR and its target CD36 as novel therapeutic and preventive targets for fatty liver disease.